1988
DOI: 10.1080/01652176.1988.9694181
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of salmonella infection of broilers by spray application of intestinal microflora: A longitudinal study

Abstract: SUMMARY The Nurmi concept for diminishing salmonella infection of poultry by application of gastrointestinal microflora from adult birds into newly hatched chicks was tested in a field study in which 8 million broilers were involved. Half of the 284 flocks was treated in the hatchery by spray application of an undefined microflora propagated in SPF chicks. A significant reduction in salmonella-contaminated flocks, as well as in the number of infected broilers in these flocks was demonstrated. No undesirable si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(22 citation statements)
references
References 4 publications
1
20
0
1
Order By: Relevance
“…was studied comprehensively by several researchers. It was reported that probiotics maintained or increased the normal intestinal flora which are normally found in the intestinal tract of hatched birds and these flora can exclude Salmonellae colonization (Goren et al, 1988;Starvic 1992;Barbour et al, 1993;Nisbet et al, 1996;Mead 2000;Seo et al, 2000). Seuna et al, (1980) who found that supplementation of the birds with normal avian gut microflora didn't prevent or only partially prevent Salmonella colonization.…”
Section: Resultsmentioning
confidence: 99%
“…was studied comprehensively by several researchers. It was reported that probiotics maintained or increased the normal intestinal flora which are normally found in the intestinal tract of hatched birds and these flora can exclude Salmonellae colonization (Goren et al, 1988;Starvic 1992;Barbour et al, 1993;Nisbet et al, 1996;Mead 2000;Seo et al, 2000). Seuna et al, (1980) who found that supplementation of the birds with normal avian gut microflora didn't prevent or only partially prevent Salmonella colonization.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, Goren et al (1984bGoren et al ( , 1988 developed a method of spray application to treat newly hatched chicks in the hatchery, either in the hatchers themselves or in delivery boxes. Spraying in the hatcher followed by drinking water administration on the farm was used by Blankenship et al (1993) and shown to be effective in controlling Salmonella infection, but there is no evidence that a double treatment of this kind is necessary to obtain maximum protection.…”
Section: Applicationmentioning
confidence: 99%
“…For example, island birds might face an immunobiome that is quantitatively or qualitatively different from the one faced by continental birds (Matson 2006;Horrocks et al 2011). However, for this to drive the observed pattern, the difference would have to exert comparable genetic effects (e.g., selection pressures) on both immunological indexes or impose systematic effects on pre-or neonatal phenotypes (e.g., via mothers [Grindstaff 2008] or directly [Goren et al 1988]). Because the typically stable index of agglutination is also substantially elevated, it is more challenging to envision a scenario in which the population differences in both immunological indexes are solely the consequence of an infection with a disease-causing organism (i.e., a result of an acute-phase response).…”
Section: Island-continent Differences In Indexes Of Development and Imentioning
confidence: 94%